Pengembangan Multimedia Interaktif Berbasis PBL pada Materi Gerak Parabola untuk Meningkatkan Hasil Belajar Peserta Didik - Abdul Halim Rohman; Kosim Kosim; I Wayan Gunada; Hikmawati Hikmawati (Universitas Hamzanwadi, 2021)
The process of learning physics at various levels of education is still faced with several difficulties, especially the use of interactive multimedia which is still lacking so that educators are required to innovate to develop interactive multimedia to increase interest in learning and student learning outcomes. This research is a development research that aims to produce interactive multimedia based on problem based learning that is valid, effective, and practical to improve student learning outcomes on parabolic motion material. The research development model used in this study is a 4D (four D) model consisting of define, design, develop and disseminate. The instruments in this development research consist of interactive multimedia, syllabus, lesson plans, LKPD, test instruments. The data collection techniques used in this study were expert validation, limited trials and student responses. The results showed that interactive multimedia had an average score of 3.12 with a very good category, the syllabus had a score of 78.08% with a very valid category, lesson plans had a score of 73.66% with a fairly valid category, LKPD had a score of 75.50% with a very valid category and the test instrument has a score of 77.60% with a very valid category. Interactive multimedia based on problem based learning is effectively used with an average score of 3.04 with a very good category and is effectively used because there is an increase in learning outcomes with an N-gain value of 0.49 having a medium category. Interactive multimedia based on problem based learning on parabolic motion material is valid, practical, and effectively used in learning so that it is suitable for use in the learning process and proven to improve students' cognitive learning outcomes